Tilapia Processing Innovation for Sustainable Development by Islamic Boarding School in Kambitin Village, Tabalong Regency, South Kalimantan Province - Flora Devica; Edi Wiraguna*; Tri Budiarto; Muhammad Iqbal Nurulhaq (Universitas Syiah Kuala, 2024)
This study explores the integration of Islamic education with practical training in fishery management at Al Islam Agricultural Technology Islamic Boarding School, focusing on tilapia cultivation in South Kalimantan, Indonesia. Despite challenges in post-harvest management leading to limited sales of raw tilapia, innovative training initiatives aim to extend product shelf life and enhance market value. A community service program evaluated from September to December 2023 assessed the sustainability of tilapia processing training among students (santri), emphasizing skills development in product innovation and hygiene practices. The program, utilizing various tools and materials, successfully introduced processed fish products such as shredded meat, nuggets, tofu meatballs, and baby tilapia crispy, garnering high participant satisfaction (79.91%) and affirming potential for sustainable fishery practices.